ID: 83: PRODUCTION OF SOLUBLE RECEPTOR FOR ADVANCED GLYCATION END-PRODUCTS FOLLOWING ACUTE AEROBIC EXERCISE IS GENDER SPECIFIC. Issue 4 (22nd March 2016) - Miranda, ER; Mey, JT; Blackburn, BK; Haus, JM; Farabi, SS; Quinn, L
Abstract : The Receptor for Advanced Glycation End Products (RAGE) is a transmembrane receptor that initiates a self-propagating inflammatory cascade and has been implicated in the onset of complications involved with aging, diabetes and neuroinflammation. Soluble RAGE (sRAGE) inhibits this inflammatory signaling by competitively binding to RAGE ligands without stimulating downstream effectors. Evidence from our lab demonstrates chronic aerobic exercise increases the cleaved isoform of sRAGE (sRAGEc). However, the effects of acute aerobic exercise on sRAGEc production have not been comprehensively examined. Furthermore, recent data suggests that estrogen may play a role in exacerbating RAGE signaling and perturbing sRAGE production in diabetic women. Therefore, the primary objective of this study was to investigate changes in plasma sRAGE with acute aerobic exercise in both lean healthy (LH) and obese insulin resistant (OB-IR) individuals. A secondary objective of the study was to compare exercise responses between men and women. 8 LH participants (4 M, 4 F) and 14 OB-IR participants (4 M, 10 F) were recruited for the study. VO2max was determined via treadmill test and participants returned to the lab on a separate day following an overnight fast and exercised at 65% VO2max for 30 minutes. Blood samples were collected before and following exercise after participants rested in seated position for 30 minutes. Quantification of plasma sRAGE and endogeonous secretory RAGE were determined via ELISA and sRAGEc was calculated by subtraction. Between-group comparisons were made via independent T Test and the effect of gender was analyzed via two-way ANOVA. At baseline the OB-IR group was older (41±3 y vs. 26±1 y, p <.001), more obese (BMI 35.1±0.9 vs. 22.2±0.9 kg . m −2, p <.001) and less aerobically fit (VO2max 27.8±1.8 vs. 50.2±2.9 mL/kg −1 . min −1, p <.001) compared the LH group. There was no main effect of group (OB-IR vs. LHC) on change in sRAGE or sRAGEc in response to exercise (ΔsRAGE 20.3±53.2 vs. 13.8±34.4 pg/mL, p =.93), (ΔsRAGEc 28.7±47.1 vs. 14.4±34.8 pg/mL, p =.33). However there was an effect of gender on the response to acute exercise. Males in both groups saw a significantly greater increase in plasma sRAGE (131.49±46.46 vs. −46.94±39.23 pg/mL, p <.05) and plasma sRAGEc (127.73±47.04 vs. −36.08±34.13 pg/mL, p <.05) compared to females. This study is the first to show that young healthy women and obese/insulin resistant women have an impaired ability to increase sRAGE plasma levels with acute aerobic exercise. Recent data has suggested that estrogen can exacerbate RAGE signaling as well as inhibit sRAGE production although the precise mechanism for this interaction is unclear and warrants further investigation.